Synthesis of β-Fluoro Amides Using Partially Hydrated Nickel Difluoride as Fluorine Source - Zhang, Wan Xuan; Su, Li; Hu, Wei Gang; Zhou, Jie (Synlett, 2012)
β-Fluoro amides were obtained from the reactions of activated aziridines with partially hydrated nickel difluoride (NiF2·nH2O, n <4) in good yields (47–82%) in the presence of tetra-n-butylammonium fluoride (20 mol%), while the non-activated aziridines did not react under the same conditions.
Keywords: nickel; fluorine; halogenation; ring opening; sulfonamide